please answer.for first correct answer i will mark as brainliest
you can do on paper and attach photo
Attachments:
![](https://hi-static.z-dn.net/files/d40/d3d43f5883baa0865750bca2e015dbfe.jpg)
Answers
Answered by
0
Step-by-step explanation:
now take x^2 common we get
x^2(q-1)=-q
x^2=-q/q-1
x^2=q/1-q
x=sqrt(q/1-q)
Answered by
0
Answer:now take x^2 common we get
x^2(q-1)=-q
x^2=-q/q-1
x^2=q/1-q
x=sqrt(q/1-q)
Step-by-step explanation:
Similar questions
Social Sciences,
6 months ago
Math,
6 months ago
Social Sciences,
1 year ago
Chemistry,
1 year ago
Math,
1 year ago
Biology,
1 year ago